Environment friendly solar car - Majumder, Md. Golam Shahriar; Alam, Md. Touhidul; Zubair, Md. Ashraf Uddin Ahmed (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2010.